2018
DOI: 10.1080/14786419.2018.1525715
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of α and β-amyrin isolated from Myrcianthes pungens leaves

Abstract: Brazil has a great variety of native plants which could be explored and among them guabiju (Myrcianthes pungens) stands out. Thus, this study consisted of isolating pentacyclic triterpenes, α and β-amyrin from guajibu leaves, and determine the antioxidant activity. The leaves were dried, pulverized and submitted to a dynamic maceration process with ethanol 96º GL, concentrated to obtain crude leaf extract (CLE). CLE was eluted with dichloromethane until total depletion, resulting in a dichloromethane fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…Others researchers found that lupeol acetate ameliorates collagen-induced arthritis through suppression of inflammatory cytokines and inhibition of bone erosion [24]. Indeed, the potential antioxidant and free radical scavenging effects of amyrin and lupeol have been demonstrated both in vitro and in vivo [25][26][27][28]. A recent report showed increased antioxidant activity and suppressed proinflammatory cytokine expressions in obese OA rats fed with SNO, further consolidating our previous findings [29].…”
Section: Introductionsupporting
confidence: 66%
“…Others researchers found that lupeol acetate ameliorates collagen-induced arthritis through suppression of inflammatory cytokines and inhibition of bone erosion [24]. Indeed, the potential antioxidant and free radical scavenging effects of amyrin and lupeol have been demonstrated both in vitro and in vivo [25][26][27][28]. A recent report showed increased antioxidant activity and suppressed proinflammatory cytokine expressions in obese OA rats fed with SNO, further consolidating our previous findings [29].…”
Section: Introductionsupporting
confidence: 66%
“…Such compounds are known for their antimicrobial and antioxidant activities (Ali et al, 2017;Pinto et al, 2017). β-Amyrin (8.09%) has been found in various plant species including Monotheca buxifolia, Myrcianthes pungens and Melia azedarach, showing antifungal, anti-inflammatory and antioxidant activities (Jabeen et al, 2011;Okoye et al, 2014;Cardoso et al, 2020;Javed et al, 2021). α-Amyrin acetate (8.25%) showed antihyperglycaemic activity in rats (Singh et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of triterpenoid was observed in propolis from Cameroon [ 44 ], a medicinal fungus, Sanghuangporus sanghuang [ 45 ], and the stem bark of Reissantia indica [ 46 ]. It is possible that cycloartenol, α -amyrin, and β -amyrin that are classified as triterpenoids in the extract may have a synergistic effect on the antioxidant activity of HEP [ 47 – 49 ]. In contrast, the low antioxidant activity of EEP may be partly derived from phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%